Un « roman idyllique » du XVe siècle et le droit matrimonial : « Paris et Vienne » de Pierre de La Cépède - Ribémont, Bernard (AMU Press, 2011)
Since the pioneering work of Myrrha Lot-Borodine identifying a particular form of the novel, with Floire et Blanchefl or as a founding text where a much more central role is given to women. I would like here to analyze Paris et Vienne, a text that critics had little studied, from the perspective of family law and matrimonial issues such that can be analyzed through the fiction that proposes to 1432, Pierre La Cépède. I will work on the short version, because condensed, only shows that the more deep springs of the text.